THE INFLUENCE OF POSITION PROMOTIONS AND TRAINING ON EMPLOYEE LOYALTY IN PT. SUMBER ALFARIA TRIJAYA TBK TEBING TINGGI BRANCH WITHJOB SATISFACTION AS A VARIABLE INTERVENING - Sri Winda Hardiyanti. Damanik; Suci Etri Jayanti. S; Fikri Haikal Siregar (CV. RADJA PUBLIKA, 2024)
This study aims to determine the effect of promotion and training on employee loyalty with job satisfaction as an intervention variable. This type of research is quantitative. This study uses data collection methods through questionnaires. The sample used in this study were 83 respondents using the non-probability sampling method. The test tools used in this study were the research instrument test, classical assumption test, hypothesis testing and path analysis using SPSS 25 software. The results showed that job promotion had a significant effect on job satisfaction. Training has a significant effect on job satisfaction. Promotion has a significant effect on employee loyalty. Training has a significant effect on employee loyalty. work goals have no significant effect on employee loyalty. work objectives are not able to mediate the relationship between job promotion and employee loyalty. work objectives are not able to mediate the relationship between training and employee loyalty.